Eating Well, Living Better: The Grassroots Gourmet Guide to Good Health and Great Food - Fenster, Michael S. (Rowman & Littlefield Publishers, 2012)
Everyone loves to eat. And everyone wants to be healthy. But how do we navigate between today’s extremes—between those offering us gastronomic gluttony and the siren song of convenient junk food and those preaching salvation only through deprivation and boring food choices? Dr. Michael Fenster draws upon his expertise and training as an interventional cardiologist and as a chef to forge a path through this wilderness to offer readers a middle path that endorses both fine dining and health eating. As a chef and foodie, and someone who has battled the bulge himself, he knows that if the food doesn’t taste great, no one will sustain any program for a lifetime. Here, Dr. Mike introduces the idea of becoming a Grassroots Gourmet. Being a Grassroots Gourmet is all about using fresh, wholesome ingredients, from local sources when you can get them. It is about the judicious use of salt, sugars, and fat to create wonderfully appealing and tasty, restaurant-worthy dishes. You do not need to be a trained chef; a few simple techniques, described here, go along way. As a physician, chef, and martial arts expert, Fenster combines knowledge from all three fields to present a cooking and dining program that recognizes our desire to eat great food without gaining weight and without sacrificing our health along the way. Revealing the latest data on previously forbidden foods like red meat and foie gras, Dr. Mike describes why these can be delicious AND healthy choices. He guides the reader step by step through a philosophy of eating and living that is sustainable and enjoyable once the commitment is made, and offers original, kitchen-tested recipes, and information about various food choices. Recipes include: Oven Roasted Mushroom Stuffed Quail with Blueberry Chimichuri Chicken Yakitori Saffron Risotto with Mushrooms, Peas, and Pearl Onions French Omelet with Truffle Butter and Brie Butternut Squash Ravioli with Sage Brown Butter Porcini Mushroom and Artichoke Heart Ragu Grilled Pork Loin Margarita Blood Orange Curry Sauce